Particularities of material and technical basis of the farms in Poltava oblasta in the epoch of free entrepreneurship (1861–1917) - Мар’євська, М. Ю. (Scientific Progress & Innovations, 2012)
The components of the material and technical basis of the cottages in the Poltava region in the second half of the XIX century and at the beginning of the XX century have been analyzed from the point of view their impact on the competitiveness of the small commodity producers in the specific historical conditions, which had been formed on the territory of the Naddniprjanska Ukraine after the abolition of serfdom in 1861.